On the design of low-frequency filters using CMOS OTAs operating in the subthreshold region - Düzenli, G; Kiliç, Y; Kuntman, H; Ataman, A (ELSEVIER ADVANCED TECHNOLOGY, 1999)
Design considerations on a circuit technique based on subthreshold operation of MOS transistors is described for the realization of low-frequency OTA-C active filters with small capacitance values of the order of 25-400 pF. The circuit technique described is applied to the alpha (8-12 Hz), beta (13-40 Hz), theta (4-8 Hz) and delta (1-4 Hz) band filters for EEG signals. Because of small capacitance values the filter circuit is suitable for realization on a single VLSI chip using the CMOS technology, and enables the user to implement the circuit on implantable biotelemetric applications. (C) 1998 Elsevier Science Ltd. All rights reserved.
Keywords: CMOS OTA; low power; subthreshold region; filter; MODEL; Engineering; Science & Technology - Other Topics